2020
DOI: 10.3390/ma13173775
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Method for Monitoring Hygro-Mechanical Reactions of Pine and Oak Wood by Acoustic Emission Nondestructive Testing

Abstract: The main issue of wood is its sensitivity to Relative Humidity (RH) variations, affecting its dimensional stability, and thus leading to crack formations and propagations. In situ structural health monitoring campaigns imply the use of portable noninvasive techniques such as acoustic emission, used for real-time detection of energy released when cracks form and grow. This paper proposes a calibration method, i.e., acoustic emission, as an early warning tool for estimating the length of new formed cracks. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Tensile tests were performed using a UTM (MTS-Measure Test Simulate ® [18]), by applying a displacement rate of 0.5 mm/min. During each tensile test, two types of fracture progressions were distinguished: brittle-like and ductile-like fracture progressions [16]. They differ in the rate of deformation of a material-the former being elastic and fast, the latter being plastic and slow-as well as in terms of the type of released energy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tensile tests were performed using a UTM (MTS-Measure Test Simulate ® [18]), by applying a displacement rate of 0.5 mm/min. During each tensile test, two types of fracture progressions were distinguished: brittle-like and ductile-like fracture progressions [16]. They differ in the rate of deformation of a material-the former being elastic and fast, the latter being plastic and slow-as well as in terms of the type of released energy.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the procedure described in [16], the distribution of each acoustic emission parameter occurring during brittle phenomena was analyzed in order to identify the acoustic fingerprint of the species. Moreover, the cumulative sum of AE parameters was used to evaluate the sensitivity of AE with respect to dryness along the longitudinal and radial directions of the beam, and hence investigate the effect/impact of EMC changes on the mechanical properties of wood.…”
Section: Equilibrium Moisture Content Model and The Acoustic Emission...mentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation showed that the most monitored acoustic Eeission parameters were amplitude (A), energy (E) and counts (C), which were frequently studied against time, crack length and load (even in their cumulative form) with their distribution often highlighted. Among the parameters less frequently studied there are the frequency characteristics [11,[16][17][18][19][20][21], other parameters such as the energy release rate (G) [22], the fracture toughness (K) [23,24], root mean square of the signal voltage (RMS) [25][26][27], density surface energy value (DSV) [16,23], stress (σ), strain (ε) [20,[28][29][30][31][32] and modulus of elasticity (MoE) [32,33].…”
Section: Subject Areas Of the Researchmentioning
confidence: 99%
“…Other works propose mathematical formulations for example as model to express the relationships between surface roughness and chip thickness [25], to compare experimental data to the theoretical ones [16], or to define the location algorithm used for the burst source location in wood specimens [30]. In Shao et al [39] a theoretical approach was presented in the study of the fractal theory applied to examine the fracture surfaces of five types of woods.…”
Section: Subject Areas Of the Researchmentioning
confidence: 99%